(-4x^4+5x^3-x^2+1)+(2x^4-7x^3+6x^2+2x)
Answer in standard form
1 answer:
Answer by Distributing Like Terms: ![-4x^4+5x^3-x^2+1+2x^4-7x^3+6x^2+2x](https://tex.z-dn.net/?f=-4x%5E4%2B5x%5E3-x%5E2%2B1%2B2x%5E4-7x%5E3%2B6x%5E2%2B2x)
![=-4x^4+5x^3+-x^2+1+2x^4+-7x^3+6x^2+2x](https://tex.z-dn.net/?f=%3D-4x%5E4%2B5x%5E3%2B-x%5E2%2B1%2B2x%5E4%2B-7x%5E3%2B6x%5E2%2B2x)
Combine Like Terms:
![=-4x^4+5x^3+-x^2+1+2x^4+-7x^3+6x^2+2x\\=(-4x^4+2x^4)+(5x^3+-7x^3)+(-x^2+6x^2)+(2x)+(1)\\\=-2x^4+-2x^3+5x^2+2x+1](https://tex.z-dn.net/?f=%3D-4x%5E4%2B5x%5E3%2B-x%5E2%2B1%2B2x%5E4%2B-7x%5E3%2B6x%5E2%2B2x%5C%5C%3D%28-4x%5E4%2B2x%5E4%29%2B%285x%5E3%2B-7x%5E3%29%2B%28-x%5E2%2B6x%5E2%29%2B%282x%29%2B%281%29%5C%5C%5C%3D-2x%5E4%2B-2x%5E3%2B5x%5E2%2B2x%2B1)
Answer: =−2x^4−2x^3+5x^2+2x+1
Formula rewritten in standard form: ![-2x^{2} -2x^{3}+5x^{2} +2x+1](https://tex.z-dn.net/?f=-2x%5E%7B2%7D%20-2x%5E%7B3%7D%2B5x%5E%7B2%7D%20%2B2x%2B1)
You might be interested in
Answer:
the final temperature is 39.0
Answer:
x = 0
Step-by-step explanation:
Answer:
last one i gussing
Step-by-step explanation:
Answer:
I'm fine how are you?
stay safe